2021
DOI: 10.29219/fnr.v65.5556
|View full text |Cite
|
Sign up to set email alerts
|

Iron intake among Lebanese women: sociodemographic factors, iron-rich dietary patterns, and preparation of hummus, a Mediterranean dish

Abstract: Background: Plant-based foods such as hummus are alternative to animal protein, and when properly prepared, they help to alleviate nutritional iron deficiency that leads to anemia, a global health problem. Objective: The objective was to assess iron intake among Lebanese women and related participant's characteristics, discern iron-rich dietary patterns, evaluate their association with nutrients intake and participant's sociodemographic characteristics, and identify the women preparing hummus traditionally and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…A new updated study showed that approximately 60% of the Lebanese Women have dietary iron intake deficiency, with low-income women being the most impacted [10].…”
Section: Introductionmentioning
confidence: 99%
“…A new updated study showed that approximately 60% of the Lebanese Women have dietary iron intake deficiency, with low-income women being the most impacted [10].…”
Section: Introductionmentioning
confidence: 99%